2017
DOI: 10.1177/2050640616670566
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the efficacy of the prognostic factor score in the Japanese severity criteria for severe acute pancreatitis: A large multicenter study

Abstract: The prognostic factor score has an equivalent ability for predicting mortality compared with the APACHE II score. Regarding the ability for predicting the development of severe complications during the clinical course of AP, the prognostic factor score may be superior to the APACHE II score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
0
26
0
1
Order By: Relevance
“…Although most patients with AP have the mild form of the disease, patients with moderate to severe AP, especially those who are admitted to the intensive care unit (ICU) due to organ failure, constitute a substantial burden to the Chinese medical system [4,5]. Early assessment of disease severity and prognosis is crucial in defining treatment strategies, because effective treatment can significantly reduce mortality in patients with AP [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although most patients with AP have the mild form of the disease, patients with moderate to severe AP, especially those who are admitted to the intensive care unit (ICU) due to organ failure, constitute a substantial burden to the Chinese medical system [4,5]. Early assessment of disease severity and prognosis is crucial in defining treatment strategies, because effective treatment can significantly reduce mortality in patients with AP [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to evaluate the risk factors of early death in SAP [10]. The Japanese severity score (JSS) [11], which covers 18 risk factors, is generally used to assess the severity of AP and predict the progress of AP to SAP. However, the JSS was complex for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by Ikeura et al 1 assessing the efficacy of the prognostic factor score in the Japanese severity criteria for acute pancreatitis (AP). By analyzing 1159 patients with severe AP, they showed that the area under the curve (AUC) for the receiver‐operating characteristic curve of the prognostic factor score for predicting AP‐related mortality was 0.78, which was comparable to that for the well‐known acute physiology and chronic health evaluation (APACHE) II score (AUC = 0.80).…”
Section: Figurementioning
confidence: 99%